Troubled water: Tracing the plastic tide on Sierra Leone’s beaches - Stephanie Lavelle; Fiona Preston-Whyte; Paul A. Lamin; Salieu Kabba Sankoh; Isha Timbo; Thomas Maes (Cambridge Prisms: Plastics)
This study provides the first investigation into quantities, types, and potential sources of anthropogenic beach litter in Sierra Leone. Beach litter surveys were conducted monthly at four sites over 11 months. A total of 72,901 litter items (1,246 kg dry weight) were categorised. Across all sites, an average of 1,657 items per 100 m (SD = 1,639) and 28.32 kg per 100 m (SD = 37.48) were recorded. Plastics accounted for 70% of the litter by count and 49% by weight. The three most abundant items by count were plastic bottles (25%), plastic caps and lids (13%), and plastic water sachets (12%). By weight, the three most abundant items were plastic bottles (36%), flip-flops (20%), and shoes (9%). Litter amounts decreased from wet to dry season. We provide the following policy recommendations: improving drinking water access and sanitation, waste management, infrastructure and behaviour change.